2001
DOI: 10.2214/ajr.177.4.1770861
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Fiberoptic Bronchoscopy Before Bronchial Artery Embolization for Massive Hemoptysis

Abstract: Fiberoptic bronchoscopy before bronchial artery embolization is unnecessary in patients with hemoptysis of known causation if the site of bleeding can be determined from radiographs and no bronchoscopic airways management is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
92
1
8

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(107 citation statements)
references
References 30 publications
2
92
1
8
Order By: Relevance
“…A contrast extravasation as a specific sign of haemorrhage is rarely seen, with reported prevalence from 3.6-10.7% because the bleeding from bronchial arteries is slow and intermittent. 1,2,10,11 The comparison of the signs of bleeding and hypervascularization of the lung parenchyma were indicators of the lesion localization and haemorrhage in all patients (11/11; 100%). Besides those findings, at least one of the following pathognomonic signs was present in all our patients: AV fistulas in 6/11 (54.5%); tortuous, hypertrophic arteries in 8/11 (72.7%); and arterial aneurysms in 3/11 (27.3%) patients.…”
Section: Discussionmentioning
confidence: 94%
“…A contrast extravasation as a specific sign of haemorrhage is rarely seen, with reported prevalence from 3.6-10.7% because the bleeding from bronchial arteries is slow and intermittent. 1,2,10,11 The comparison of the signs of bleeding and hypervascularization of the lung parenchyma were indicators of the lesion localization and haemorrhage in all patients (11/11; 100%). Besides those findings, at least one of the following pathognomonic signs was present in all our patients: AV fistulas in 6/11 (54.5%); tortuous, hypertrophic arteries in 8/11 (72.7%); and arterial aneurysms in 3/11 (27.3%) patients.…”
Section: Discussionmentioning
confidence: 94%
“…3) can assess the potential for a possible source of bleeding of the bronchial artery as well as identifying possible branches supplying the spine. Active bleeding which can be recognized by extravasation from a branch of the bronchial artery can be demonstrated in about 3.6 -10.8 % of cases and then only during an episode of massive hemoptysis [61,85,86]. The diameter of the bronchial arteries in cases of chronic inflammatory pulmonary disease is generally between 2 -3 mm [17], however it can be several millimeters, especially in patients with cystic fibrosis ( • " Fig.…”
Section: Technologymentioning
confidence: 99%
“…A promptly performed bronchoscopy (BSK) supports finding the cause and side localization of the bleeding [16,60], although correct side localization of the bleeding can be achieved in only about half the patients [58,61]. This can be performed easily and quickly as an initial fiber optic examination (fiber optic bronchoscopy -FOB) and as a rigid bronchoscopy in the case of more massive hemoptysis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[100][101][102] Routine chest x-ray is readily available and helpful; however, in a retrospective evaluation of 208 patients with hemoptysis, Hirshberg et al 103 found that radiography was diagnostic in only 50% of cases. Bronchoscopy is by far more accurate, but the role of fiberoptic bronchoscopy in the setting of massive active hemoptysis is still controversial.…”
Section: Diagnosis Of Hemoptysismentioning
confidence: 99%